Simple and complex pig starters compared - Koch, B.A.; Hines, Robert H. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Baby pigs have the ability to grow rapidly and efficiently. Creep rations at an early age enhance their potential. Most commercial creep rations contain feedstuffs to increase palatability and acceptability. Are these ingredients necessary or will rather simple starters produce similar gains? Five starters were compared, varying from a simple corn-milo- soybean meal ration to a ration containing several palatability aiding ingredients--from 10 days of age to weaning at 28-35 days; and from 6 weeks to 10 weeks of age.
Swine Industry Day 1969 is known as Swine Day, 1969
Keywords: Swine; Creep rations; Palatability